APPLICATION OF HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) IN BRSUD TABANAN NUTRITION INSTALLATION (CASE STUDY ON RICA-RICA CHICKEN PROCESSING) - Ni Kadek Yuli Yantari; Ni Putu Agustini; I Gusti Putu Sudita Puryana (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
The concept of ensuring the safety and quality of food that is considered more effective and